Mechanical work of body center of mass in classical cross-country skiing - Pellegrini, B.; Zoppirolli, C.; Bortolan, L.; Zamparo, P.; Schena, F. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: Human locomotion can be analyzed by computing the mechanical work necessary to sustain it. Starting from the knowledge of the center of mass (COM) displacement it is possible to calculate work associated to the potential and kinematic energy changes. For walking and running this approach has allowed to identify the models associated to these forms of locomotion as well as to understand the transfer between these energy forms. The aim of this study was to analyze the mechanical work associated to COM motion in cross-country skiing for the diagonal stride (DS) and the double poling (DP= techniques.